O acolhimento aos familiares das pessoas atendidas em centro de atenção psicossocial álcool e outras drogas - Lisbôa, Gabrielle Leite Pacheco (2014)
This exploratory qualitative research was carried out in a State of Alagoas Alcohol and Other Drugs Psycho Social Care Center of the 3rd Type. It aimed at understanding how the reception of the family whose relative is under treatment in the Alcohol and Other Drugs Psycho Social Care Center. Eight professionals and six family members took part in this study. This study was previously approved by the Center of Higher Studies of Maceió - CESMAC‟s Committee on Ethics in Research and Teaching (COEPE) under the protocol number 1574/12. The ethical principles were respected according to what is stated on the Resolution CNS/MS 466/2012. The data collection was accomplished between June and November, 2013, through semi-structured interviews with the use of previously elaborated script and records from the field journal. Bardin was used for the analysis and its discussion was founded on Merhy. The results highlighted the reception as the act of receiving. For the professional, it is a matter of administrative reception, sorting out and transmission of information, whereas for the family relations, it has to do with being always welcome. The practice, present within the relations in which there is the professional-user gathering, is materialized in the family groups and in listening. The overwhelming demand, the professionals‟ lack of preparation, the reception focused on the dependency, difficulties for the interdisciplinary work and the absence of an effective net were identified as kinds of noise produced in the work process, thus making the family reception more difficult. The increase of the bonds, the territorialisation, the articulation with other self-help groups and operationalization of the family groups were pointed out as ways to receive the families. The current study does not close the discussion about the mentioned matter and it opens spaces to make future investigations possible. At promoting professionals and families‟ self-reflection about the reception, it evokes an intervention on the objective reality, the improvement of the inter-personal relations, changes in the work process and the strengthening of the bonds so as to make the service at CAPS more coherent with the reception.